PENGGUNAAN STRATEGI PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INDONESIA DI SMPN 3 NATAR LAMPUNG SELATAN - Juarnita, Leny; Rona Romadhianti; Mega Yanti; Suri Laili Mustika; Desi Yuliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Speaking ability is one of the essential language skills in Indonesian language learning; however, in practice, students’ speaking ability remains relatively low due to a lack of confidence, fluency, and active participation in the learning process. This problem was also found among eighth-grade students of SMPN 3 Natar, South Lampung, who demonstrated limited participation and difficulty in expressing ideas orally. This study aimed to improve students’ speaking ability through the implementation of cooperative learning strategies. The research employed Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were eighth-grade students of SMPN 3 Natar, South Lampung. Data were collected through speaking ability tests, observations of students’ and teachers’ activities, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques to identify improvements in students’ speaking ability in each cycle. The results showed that the application of cooperative learning strategies significantly improved students’ speaking ability, as indicated by increased confidence in speaking, fluency, clarity in expressing ideas, accuracy of pronunciation, and vocabulary mastery from the pre-cycle to Cycle II. Therefore, cooperative learning strategies are effective in enhancing students’ speaking ability in Indonesian language learning.